Faces and eyes Detection in Digital Images Using Cascade Classifiers - Alhamzawi Hussein Ali Mezher (Universitas Sriwijaya, 2018)
In this Article we present a way to implementation and detect the face and eyes on digital image, based on Haar-like features extraction and cascade classifier, these techniques used in 100 % and 92% for faces and eyes detection respectively for the best all cases using low processing time , we used cheap equipment in our work (Acer TravelMate web camera ) . OpenCV library(computer vision library) and Python language used in this work.